2008
DOI: 10.12693/aphyspola.113.1671
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Time on Nd2O3-SiO2Composite Prepared by the Solgel Process

Abstract: Using solgel method Nd2O3−SiO2 binary oxide systems were prepared. The binary oxide transformed from the amorphous phase to nanocrystalline phase upon heat treatment in air. Characterization of the Nd2O3-SiO2 was carried out by using X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The effect of the sintering temperature and time on the evolution of the binary oxide system was discussed. It is found that sintering time plays a pivotal role to obtain Nd 2 O 3 -SiO2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The initial structure of the developed phase may be described by reflections centered about 2Â ∼ 21. Here, it is worth pointing that in the previous investigation [11] such major reflections were not observed in high Nd 2 O 3 loaded sample (6 wt%) as well as when annealed in air at comparatively higher temperature (900 • C). A significant phase change in Nd 2 O 3 -SiO 2 observed when the sintering time was further increased from 10 to 20 h and calcinations was performed at the constant sintering temperature 850 • C. Finally, the sample was fired for 20 h (typically) strongly supports the growth rate of orthorhombic Nd 2 Si 3 O 9 phase in compare to the other phase.…”
Section: Xrdmentioning
confidence: 60%
See 2 more Smart Citations
“…The initial structure of the developed phase may be described by reflections centered about 2Â ∼ 21. Here, it is worth pointing that in the previous investigation [11] such major reflections were not observed in high Nd 2 O 3 loaded sample (6 wt%) as well as when annealed in air at comparatively higher temperature (900 • C). A significant phase change in Nd 2 O 3 -SiO 2 observed when the sintering time was further increased from 10 to 20 h and calcinations was performed at the constant sintering temperature 850 • C. Finally, the sample was fired for 20 h (typically) strongly supports the growth rate of orthorhombic Nd 2 Si 3 O 9 phase in compare to the other phase.…”
Section: Xrdmentioning
confidence: 60%
“…The stem of this study is in the results of our earlier report [11], in which, we reported that the thermal annealing history plays crucial role in altering the fundamental of size controlled on Nd 2 O 3 -doped silica powder prepared by the sol-gel protocol method. In that investigation [11], it was observed that the structures of the Nd 2 O 3 -doped silica powder depend on annealing temperature (900 • C) and time (12 h). The main goal was to characterize fully the structure of the new superficial orthorhombic silicates phase.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The stem of this study is in the results of our earlier report [18], in which we demonstrated the eect of temperature and time on Nd 2 O 3 SiO 2 nanocomposites. The annealing temperature and time dependence of the formation of Nd 2 O 3 nanocrystallites as well as their distribution in fused silica matrix were observed.…”
mentioning
confidence: 61%
“…[18]. Silver silicates were prepared by mixing high purity reagents (CH 3 CH 2 O)Si tetraethoxy silane (TEOS) (Aldrich 99.999), ethanol (Aldrich 99.9995), and deionized water.…”
Section: Preparation Of Bulk Samplesmentioning
confidence: 99%